Pengaruh Pijat Medic Pediatric sebagai Terapi Konstipasi pada Bayi Usia 6-12 Bulan - Mayga Aningtia Saputri; Catur Yulinawati; Andi Wilda Arianggara (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Constipation is a health problem that often occurs in infants. Basedon an initial survey at the Sei Langkai health center, data was obtained that out of 10 babies, 7 of them had experienced constipation and most mothers did not know how to deal with constipation in infants. The purpose of the study was to determine the effect of Pediatric Medical Massage asa Constipation Therapy. The subjects in this study were infants aged 6-12 months. Thisresearch was carried out in the Working Area of the Sei Langkai Health Center in Batam City using Quasi Experiments with pre and posttest control design. This research was conducted in.The results showed that in the intervention group obtained a value of p = 0.000 < 0.05 which showed that there was an effect of Pediatric Medical Massage as a Constipation Therapy in infants aged 6-12 months, while in the control group the test results showed that the value of p = 0.083 > 0.05 so that it could be stated that There is no effect on the treatment of control groups against constipation in infants aged 6-12 months. Theconclusion of the study is that pediatric medical massage can be a method in overcoming constipation in infants so that mothers can overcome the incidence of constipation in infants at home